Pengaruh Pendekatan Kontekstual Berbasis Hands on Activity terhadap Keterampilan Proses Sains dan Kemampuan Kognitif Siswa - Asti Asmawati; I Wayan Karmana; Hunaepi Hunaepi (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2017)
The purpose of this study was to determine the effect of using the contextual approach based on hands-on activity toward students’ science process skills and cognitive learning outcomes of class VII of SMP 1 Kediri in the academic year 2016/2017. This type of research is quasi-experimental. The research sample consisted of 51 students divided into experimental classes and control classes. The technique of collecting data in the form of tests to assess students 'cognitive learning outcomes, and performance assessment for students' science process skills. The results showed that the experimental class posttest average was 47.59 and the control class was 55.8. The students’ science process skills score for the experimental class with an average of 77.33 with a high category. The results of the t-test are obtained tcount <ttable (-2.012 <1.98), so that the contextual approach based on hands-on activity does not affect on the students’ cognitive learning outcomes of class VII of SMP 1 Kediri in the academic year 2016/2017.